The impact of radiation effect on MHD stagnation-point flow of a nanofluid over an exponentially stretching sheet in the presence of chemical reaction - Narender, Ganji; Sarma, Sreedhar; Govardhan, K. (Zielona Góra: Uniwersytet Zielonogórski)
The present study is to investigate the effect of the chemical reaction parameter on stagnation point flow of magnetohydrodynamics field past an exponentially stretching sheet by considering a nanofluid. The problem is governed by governing coupled nonlinear partial differential equations with appropriate boundary conditions.
Keywords: numerical solutions; MHD; radiation effect; stagnation-point flow; chemical reaction; nanofluid